2012
DOI: 10.1021/ol301801r
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Acylation of Cyclic Enamides with α-Oxocarboxylic Acids by Palladium-Catalyzed C–H Activation at Room Temperature

Abstract: An efficient catalytic decarboxylative acylation of unactivated sp(2) (alkenyl) C-H bonds has been developed. Various substituted α-oxocarboxylic acids with different electronic properties react under mild conditions to afford a diverse range of β-acyl enamide products in good yields. The reaction is proposed to proceed via a cyclic vinylpalladium intermediate, facilitating the decarboxylative dehydrogenative process with enamide coupling partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(59 citation statements)
references
References 50 publications
0
59
0
Order By: Relevance
“…[4] In this area of research, various directing groups such as ketones, [5] carboxylic acids, [6] amides, [7] pyrrole/pyridine, [8] anilides, [9] carbamate, [10] urea [11] and azine N-oxide [12] can provide an anchor for catalytic ortho-metalation of aromatic rings. Decarboxylative C À H bond acylations of arylpyridines, [18] acet-A C H T U N G T R E N N U N G anilides, [19] and enamides [20] using a-oxocarboxylic acids as acyl surrogates were also reported. In 2009, Cheng first reported a palladium-catalyzed cross-coupling reaction between arenes containing a pyridine directing group and aryl aldehydes to afford aryl ketones.…”
mentioning
confidence: 99%
“…[4] In this area of research, various directing groups such as ketones, [5] carboxylic acids, [6] amides, [7] pyrrole/pyridine, [8] anilides, [9] carbamate, [10] urea [11] and azine N-oxide [12] can provide an anchor for catalytic ortho-metalation of aromatic rings. Decarboxylative C À H bond acylations of arylpyridines, [18] acet-A C H T U N G T R E N N U N G anilides, [19] and enamides [20] using a-oxocarboxylic acids as acyl surrogates were also reported. In 2009, Cheng first reported a palladium-catalyzed cross-coupling reaction between arenes containing a pyridine directing group and aryl aldehydes to afford aryl ketones.…”
mentioning
confidence: 99%
“…2 Later Ge et al reported the Pd-catalysed decarboxylative acylation of acetanilides and 2-aryl pyridines at the orthoposition of the phenyl ring with α-oxocarboxylic acids via ligand-assisted ortho-C(sp2)-H activation in the presence of an oxidant. 3 Subsequently different directing groups including azobenzenes, 4 azoxybenzenes, 5 carboxylic acids, 6 cyclic enamides, 7 O-methyl ketoximes, 8 O-phenyl carbamates, 9 phenylacetamides, 10 2-aryloxypyridines, 11 pyridine-N-oxides, 12 indolines, 13 thioethers, 14 N-nitroso anilines, 15 tetrahydroquinolines 16 and indoles 17 have been used for performing the acylation via ligand-assisted activation of the ortho-C(sp2)-H bond leading to formation of biaryl ketones with high regioselectivities under mild reaction conditions. β-Carboline, a privileged scaffold, is core unit of several natural alkaloids and bioactive compounds endowed with diverse pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…[4~7] Directing group-assisted activation of ortho C-H bonds has been widely investigated, and various directing groups such as acylamino, [4,8] pyridyl, [5,9] oxime [6,10] and ketone [11] groups have been used for palladium-catalyzed C-H bond activation. On the other hand, the source of acylation has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%